'Wading through children's tears': the emotional experiences of elementary school inspections, 1839–1911. Issue 5 (2nd September 2020) - Grigg, Russell
ABSTRACT: This paper explores the emotional experiences of elementary school inspections, from the appointment of the first State school inspectors in 1839 to 1911 when Edward Holmes, the retiring chief inspector, signposted the prospects of a new era in elementary education. The paper is arranged in two parts: the first provides an outline of the origins and development of elementary school inspection, while the second discusses the potential contribution of emotions scholarship to inform our understanding of elementary schooling seen through the lens of inspection. Whereas previous studies have concentrated on the inspectorate's administrative history in relation to school development, this paper's contribution is to highlight what inspection sources reveal about elementary schools as sites of emotional expression and experience. While acknowledging the challenges a history of emotions framework presents, the paper concludes that such an approach offers a fresh perspective on inspection and school regimes in the past.